Model-plant Mismatch Detection, Isolation and Estimation using Multivariate ARMAX Mismatch Modeling - KAMAL IQBAL, NUR HIDAYAH (2016)
The used of model in Model Predictive Controller (MPC) is significant as poor model can lead to degradation of the product outputs and even potential in harming the equipment used as well as the whole plant production. The study of model-plant mismatch (MPM) detection is crucial to avoid the tedious process of whole model reidentification thus remodeling is focused only to the affected submodel.